2014
DOI: 10.1523/jneurosci.5434-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Engagement of Human Motion Detectors across Space-Time Coordinates

Abstract: Motion detection is a fundamental property of the visual system. The gold standard for studying and understanding this function is the motion energy model. This computational tool relies on spatiotemporally selective filters that capture the change in spatial position over time afforded by moving objects. Although the filters are defined in space-time, their human counterparts have never been studied in their native spatiotemporal space but rather in the corresponding frequency domain. When this frequency desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 70 publications
0
22
2
Order By: Relevance
“…An interesting possibility is that the temporal context of the moving trajectory allows the history of the stimulus outside the receptive field to influence how information is processed when the stimulus is in the receptive field. Such mechanisms have been suggested by psychophysical studies 19 20 21 22 . Further studies are required to test this possibility.…”
Section: Discussionmentioning
confidence: 84%
“…An interesting possibility is that the temporal context of the moving trajectory allows the history of the stimulus outside the receptive field to influence how information is processed when the stimulus is in the receptive field. Such mechanisms have been suggested by psychophysical studies 19 20 21 22 . Further studies are required to test this possibility.…”
Section: Discussionmentioning
confidence: 84%
“…More specifically, prior psychophysical work has demonstrated that perceptual analyzers can be successfully characterized as oriented sensors (Adelson & Bergen, 1991), where orientation may be defined e.g. across space-space (Neri, 2015) or space-time (Burr et al, 1986; Neri, 2014b). More relevant to the present investigation, it has also demonstrated that noisy processes spanning different dimensions of the target stimulus, such as its native space-space or its orientation subspace, can be leveraged to probe the same perceptual operation and constrain a unique computational description of that operation (Neri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…69,98 Indeed, characterizing human motion detectors in space-time coordinates 99 led to the discovery of a previously unknown brief increase in detector amplitude at motion onset. 100 The perceptual relevance of retinotopic encoding of motion trajectories in V1 (Ref. 101) was, furthermore, demonstrated using a "pathguided" apparent motion paradigm in combination with fMRI.…”
Section: 21mentioning
confidence: 99%